Interannual variability of the Barents Sea branch water in the northeastern part of the Barents Sea and the St. Anna Trough - Zinaida Zabudkina; Zinaida Zabudkina; Alexander Osadchiev; Alexander Osadchiev; Alexander Osadchiev; Vladimir Ivanov; Vladimir Ivanov; Mikhail Makhotin; Viktor Merkulov (Frontiers in Marine Science)
In this work, we describe the inter-annual variability of the Barents Sea branch water (BSBW), which is one of the main branches of the Atlantic water that flows from the North Atlantic to the Western Arctic. We analyze an extensive data set of in situ data measurements performed during warm season from 1977 to 2024 in the northeastern part of the Barents Sea and in the St. Anna Trough. This region has experienced rapid climate change during recent decades, expressed by the decrease of sea ice and increasing heat inflow from the North Atlantic. Previously, BSBW effectively cooled in the Barents Sea and had a consistently negative temperature at its eastern boundary. However, significant warming was detected in the northeast part of the Barents Sea after 2000. We demonstrate that temperature of BSBW in the northeastern part of the Barents Sea and further in the St. Anna Trough largely increased during the last 20 years. In particular, BSBW with positive temperatures has been regularly observed in the St. Anna Trough since 2008. We reveal a link between the initial temperature of the Atlantic water masses at the western boundary of the Barents Sea on the one hand and BSBW temperature at the eastern boundary of the Barents Sea on the other hand. In addition, the temperature increase of BSBW is associated with (1) strengthening of local southwesterly winds, leading to decrease of ocean-atmosphere heat loss and (2) decreased intensity of cold dense water formation at the shallow banks of the Barents Sea. Finally, we confirm the results of previous model studies, which demonstrated the shift of the cooling zone from the Barents Sea to the St. Anna Trough. In particular, we show that during the recent years cooling of BSBW continues in the St. Anna Trough by mixing with cold dense water. The observed warming of BSBW accompanied by its salinity decrease, which is observed during the last 15 years, could significantly affect thermohaline structure and circulation in the Arctic Ocean.